Race elements in the formation of the English language, and the effects of these elements upon English literature - Brenner, Flora Edna (My University, 1906)
Introduction: English is not a language derived from any single source. Only intracing its development, however, do we come to realize the vast number of elements that enter into its formation. Almost every written or spoken tongue on the face of the earth, has, in a greater or less degree, imparted some quality, in some particular manner, to the English. Despite the fact of its borrowing from all these sources, English is primarily Indo-European or Aryan. The Aryans were a primitive race, of whom very little is known. Even their abode is disputed, some authorities ascribing it to Europe, and some to Asia. From these people, descendants have scattered to all parts of the earth and developed different tongues for themselves, but there still remains resemblances in certain words and grammatical forms. It is my purpose in this paper, to give an account of only the most important of the racial elements, directly entering into, and influencing the formation, and development of our language, and literature. The Keltic Element. The British Isles, the cradle of the English language, was, at the earliest record, inhabited by the Kelts, a race of people possessing many interesting characteristics. Their manners and customs were rude, and their homes were huts of timbers and reeds. They were divided, into tribes, each tribe, having its chief who called his people together, to confer upon matters of general concern. War was their main occupation, and swords, spears, axes, and chariots, with scythes projecting, were their weapons. Their mode of summoning warriors, was by sending a messenger, who carried a stick burnt at the end, and dipped in blood. This, they called the "Cran tara". The religion of the Kelts was Druidism, and priests were arbiters of disputes, and judges of crime. They taught Eternal Transmigration of souls, and made appeals to their gods, by offering human sacrifice. There were also Keltic Bards who went about singing the praises of heroes, using a musical instrument consisting of a wheel striking upon strings. The disposition of the Kelts exhibited varied contrasts. They were passionate and emotional, varying from great vivacity, and hilarity, to melancholy and tenderness. They were lovers of gay colors, and of gorgeous displays in any form. They have shown these characteristics in their literatures even sacrificing the best style to an elaborate manner of expression. They were remarkable for their genius, and the beauty of their writings, but lack d a balance of patience and stability, so essential to strong national government.
Citation: Brenner, Flora Edna. Race elements in the formation of the English language, and the effects of these elements upon English literature. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Literature; Race; English; Keltic; Tutonic; Danish; Norman-French; Latin; Theses